Interjections in peruvian castilian - Meza Lagos, Consuelo (2017)
In this research, we rescued some interjections that have been or are being used at the localor regional Castilian of Peru, and other interjections typical Peruvian General Castilian.The collected words for this paper express surprise, disgust, rejection, disapproval, andcold, among other meanings. We seek to establish their possible etymon and localization.Obtaining these interjections has been possible by reading different literary works ofrecognized writers like Alegria, Lopez Albujar, Palma and others who do not have theliterary recognition of the above, but who contribute by picking up regional idioms. It isnoteworthy to point out that the corpus was taken from my personal contribution to thedatabase of the Peruvian Society of Lexical Studies.